Effectiveness of the Use of the Internet of Things (IoT) in the Agricultural Sector - Adimas Ketut Nalendra; M. Nur Fuad; Dona Wahyudi; Ni’ma Kholila; M. Mujiono (GoAcademica Research & Publishing, 2022)
The current internet architecture has been developed into the Internet of Things (IoT). The IoT idea seeks to improve effectiveness, accuracy, and financial gains. This research aims to analyse the Effectiveness of the Use of the Internet of Things (IOT) in the Agricultural Sector. This study employs qualitative methods with descriptive analysis techniques. The data collection method uses literature reviews from various reputable national and international journals. This research revealed that with the rise of the Internet of Things and the digital transformation of rural areas, using these technologies to remotely monitor agricultural development, soil moisture, and crop danger has become feasible. Automation of human intervention, particularly when leveraging the Internet of Things, can improve the efficacy of agriculture and farming processes.